Strategic communication and innovation in micro and small-sized enterprises (SME) from the perspective of Local Innovation Agents (ALI) - Porém, Maria Eugênia (2018)
This paper aims to understand strategic communication as an innovation driver in micro and small enterprises (MSEs). To do so, we developed both the theoretical research based on bibliographic survey and the applied research with exploratory purposes, which relied on a semi-structured survey with 19 local innovation agents that were active in MSEs from Bauru and its neighboring towns. Additionally, a content assessment was performed for interpreting the results. This study concluded that MSEs did not perceive any relations between strategic communication and innovation. Companies see communication as a tool for promoting products and services and they apply the strategy intuitively.